Pengaruh konsentrasi PEG 400 sebagai kosurfaktan pada formulasi nanoemulsi minyak kepayang - Maharini; Rismarika; Yusnelti (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2020)
Kepayang oil has a high content of linoleic and oleic acids. Linoleic and oleic acids act as emollients in the cosmetic field. Nanotechnology is one of the latestinnovations that can be used in cosmetics preparation delivery systems because it can improve the drug delivery process. This study aims to examine the effect of PEG 400 on the formulation of Kepayang oil nanoemulsion. The concentrations of tween 80 and variation concentrations of PEG 400 used in F1, F2, and F3 are 36%: 0%, 36%: 24% and 36%: 14% using the SNEDDS method. The characteristics of nanoemulsion preparations include organoleptic, particle size, polydispersity index, and zeta potential. The result of nanoemulsion production has the organoleptic form in bright yellow color and has a distinctive odor, the particle size in F1, F2 and F3 are 11.8, 13.2 and 11.3 with a polydispersity index of 0.315, 0.147 and 0.121 and zeta potential -16.2, 13.4 and 1.8. The effect of variations in surfactant concentration in the nanoemulsion formulations of kepayang oil is that the higher the level of PEG 400, it will reduce the pH and viscosity of the preparation, increase the particle size, the uniformity of droplet size uniformity, but does not affect the potential zeta value. The best formula is F2.